Languages in a globalising world - Maurais, Jacques; Morris, Michael A. (Cambridge University Press, 2003)
This book considers the effects of present-day trends in global politics on the relative status of languages, and the directions in which the linguistic hierarchy might develop in the future. Its interdisciplinary approach will appeal to researchers and students of sociolinguistics and language planning as well as of international relations.